Prehabilitation as a key component of the Enhanced Recovery After Surgery (ERAS) program in patients with lung cancer: a narrative review - Gabryel, Piotr; Zielińska, Dominika; Szlanga, Lidia; Werblińska, Alicja; Woźniak, Jakub; Bryl, Maciej; Piwkowski, Cezary (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
Lung cancer remains a major health challenge despite recent advances in diagnostics and treatment. Surgical resection, particularly in early stages, offers the best chance for cure. Enhanced Recovery After Surgery (ERAS) programs have been shown to improve outcomes in various surgical areas. This narrative review summarizes current evidence on the role of prehabilitation within ERAS for lung cancer surgery and presents the organizational model from a high-volume academic thoracic surgery center. Key elements of prehabilitation include smoking cessation, nutritional optimization, physical activity enhancement, and patient education, all delivered by a multidisciplinary team. Despite organizational challenges, preoperative ERAS programs demonstrate benefits for patients and hospitals, supporting their broader implementation in thoracic surgery.